ФИЗИЧЕСКАЯ СУЩНОСТЬ СТАЦИОНАРНОГО ЭЛЕКТРИЧЕСКОГО ПОЛЯ И ТЕРМИНОЛОГИЧЕСКОЕ ОПРЕДЕЛЕНИЕ СВЯЗАННЫХ С НИМ ВЕЛИЧИН - Сотников, В.В. (Інститут електродинаміки НАН України, Київ, 2017)
Stationary electric field of inner conductor volume of electric circuit is considered. It's shown that the field is created not by stationary currents but charges predominantly dispensed on conductor surface. Critical analysis of voltage and voltage drop terms is performed. The incorrectness of their definition by the international electrotechnical vocabulary and GOST is shown. Scientifically justified definitions are given. References 11, figures 2.